2009
DOI: 10.1002/14651858.cd006712.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Pain control in first trimester surgical abortion

Abstract: Conscious sedation, GA and some non-pharmacological interventions decreased procedural and postoperative pain, while being safe and satisfactory to patients. Data on the widely used PCB is inadequate to support its use, and it needs to be further studied to determine any benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Regimens that include preoperative oral NSAIDs and intraoperative paracervical block with a local anesthetic are widely used but have been shown to provide incomplete pain relief. 4,7 Several nongynecologic studies report improved pain control when ketorolac is administered locally. 16 Our study demonstrated greater pain reduction associated with cervical dilation among participants who received paracervical block with combined ketorolac and lidocaine compared with those who received an oral NSAID and lidocaine-only paracervical block.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regimens that include preoperative oral NSAIDs and intraoperative paracervical block with a local anesthetic are widely used but have been shown to provide incomplete pain relief. 4,7 Several nongynecologic studies report improved pain control when ketorolac is administered locally. 16 Our study demonstrated greater pain reduction associated with cervical dilation among participants who received paracervical block with combined ketorolac and lidocaine compared with those who received an oral NSAID and lidocaine-only paracervical block.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Despite widespread use, pain regimens consisting of preoperative nonsteroidal antiinflammatory drug (NSAID) and paracervical block with local anesthesia may not be sufficient. 4 Many clinics use adjunctive medications to improve pain control, including oral and intravenous narcotics, antiinflammatory agents, and anxiolytics. However, it is unclear whether supplemental medication results in a clinically significant decrease in patient discomfort.…”
mentioning
confidence: 99%
“…Until recently, however, the data were conflicting on its efficacy. 49 Then, in 2010, Renner and colleagues 14 conducted a randomized controlled trial of 120 women undergoing surgical abortion up to 10 weeks 6 days' gestation. All women received premedication with 800 mg ibuprofen and 1 mg lorazepam at least 30 minutes prior to aspiration.…”
Section: Uterine Aspirationmentioning
confidence: 99%
“…15,16,49 Naproxen 550 mg or ibuprofen 600 to 800 mg is administered by mouth between 30 and 60 minutes prior to aspiration. Oral administration of NSAIDs appears to be sufficient for preoperative medication.…”
Section: Uterine Aspirationmentioning
confidence: 99%
“…Cochrane Reviews conclude there is inadequate evidence of benefit with local anaesthetic. However, data available on abortion under local anaesthetic supports that deep paracervical injection combined with a relatively high concentration of intrauterine lidocaine infusion improves pain scores 3. So my own practice where injection is needed is to insert a paracervical block.…”
mentioning
confidence: 99%